There is an alternative: A two-tier European currency community - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2018)
The performance of EMU member economies is shaped by different and structurally entrenched "growth models" whose success depends on specific macro-regimes - restrictive for export-led growth, accommodating for demand-led growth. These two types of models cannot be equally viable under a uniform macro regime, and their divergence threatens the stability of the EMU. The present attempt to enforce structural convergence in the euro-zone appears economically ineffective and lacks democratic legitimacy on the national and the European level. Assuming that complete integration in a democratic federal state is presently unattainable, the paper presents the outline of a more flexible European Currency Community that would include a smaller and more coherent EMU and the member states of a revised "Exchange Rate Mechanism II" (ERM) whose currencies are flexibly linked to the euro. It would restore the external economic viability of autonomous domestic policy choices, and it would protect its members against speculative currency fluctuations. – – Die Eurozone vereint strukturell heterogene Ökonomien, die entweder auf exportbasiertes Wachstum und stabilitätsorientierte Geld- und Fiskalpolitik oder auf nachfragegestütztes Binnenwachstum und dementsprechend akkommodierende Makropolitik angewiesen sind. Unter einem einheitlichen europäischen Makroregime können nicht beide Typen gleichermaßen gedeihen und ihre Divergenz gefährdet die Stabilität der Währungsunion. Die gegenwärtigen Euro-Regeln sollen eine strukturelle Harmonisierung erzwingen, aber ihr ökonomischer Erfolg ist zweifelhaft und sie sind weder auf der nationalen noch auf der europäischen Ebene demokratisch legitimierbar. Anstatt der gegenwärtig unerreichbaren Vollendung der Integration in einem demokratischen Bundesstaat skizziert der Aufsatz das Konzept einer flexiblen "Europäischen Währungsgemeinschaft". Diese würde eine kleinere und strukturell homogenere Währungsunion mit den Mitgliedern eines verbesserten Europäischen Wechselkursmechanismus (WKM II) vereinen, deren Währungen flexibel an den Euro gekoppelt sind. Eine solche Lösung würde den Handlungsspielraum autonomer nationaler Politik erweitern und böte zugleich Schutz vor spekulativen Attacken auf die Währungen der Mitglieder.
hdl:21.11116/0000-0001-D8E0-E
Keywords: 300; autonomy; currency coordination; EMS; EMU; ERM; EU; legitimacy; Autonomie; EWS; EWU; Legitimität; Währungskoordination; WKM